Laju Dekomposisi Gambut dan Dampaknya Pada Status Hara pada Berbagai Tingkat Pelindian - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This study aimed to simulate the field condition of the peat in the laboratory scale. Sa prist peat was taken from deep peat of West Kalimantan, and topogeneous peat from Rawapening (Central Java), these peats are kept in the saturated condition. The peat was placed up to 85 cm in the PVA tube of 010 cm and 0 7,5 cm. The first 25 cm of peat in the tube was mixed with the lime with the rate of 0 %, 50 %, and 100 % of total extractable acidity, and urea (100 kg/ha), KCl (100 kg/ha, and SP (200 kg/ha). The degree of aeration was done through different level of water table, i.e., and 20 cm above the peat surface